Confining Phosphanes Derived from Cyclodextrins for Efficient Regio‐ and Enantioselective Hydroformylation1. (3rd March 2014) - Jouffroy, Matthieu; Gramage‐Doria, Rafael; Armspach, Dominique; Sémeril, David; Oberhauser, Werner; Matt, Dominique; Toupet, Loic
Abstract Two confining phosphane ligands derived from either α‐ or β‐cyclodextrin produce singly PIII‐ligated metal complexes with unusual coordination spheres. High‐pressure NMR studies have revealed that rhodium hydride complexes of the same type are also formed under hydroformylation conditions. This unique feature strongly favors the formation of the branched aldehyde at the expense of the linear one with high enantioselectivity in the rhodium‐catalyzed hydroformylation of styrene.